Comparison of clinical outcomes after anterior cruciate ligament reconstruction of autogenous hamstring tendons and peroneus longus - kC, Saugat; Neupane, Gaurav; Dev Sharma, Bishnu; Prakash Dawadi, Tej; Rijal, Sanjeeb (Journal of Chitwan Medical College, 2025)
Introduction: The anterior cruciate ligament (ACL) is crucial for maintaining knee joint stability against translational and rotational forces, causing knee instability, meniscal tears, and early osteoarthritis if untreated. Hamstring tendons have gained widespread popularity due to their favourable biomechanical properties, reduced harvest site morbidity and excellent clinical outcomes. The peroneus longus tendon has been explored as an alternative autograft. Method: A comparative prospective study conducted in the Department of Orthopaedics, Chitwan Medical College, Nepal, from May 2021 to Apr 2023, following ethical approval. Patients with ACL injuries were alternatively allocated into two groups: hamstring and peroneus longus autograft. Standard fixation techniques for ACL reconstruction and rehabilitation protocols were applied. Postoperative assessments were done at 2 weeks, 6 weeks, 3 months, 6 months, and 1 year. Outcome measures included the Lysholm Score, knee stability tests (Anterior drawer test and Lachman test). Data were analysed using SPSS 21. Independent t-test, chi-square test and repeated measures ANOVA were used. Statistical significance was set at p≤0.05. Result: Out of 54 patients (27 in each group), both groups demonstrated excellent functional recovery at one-year follow-up, with no statistically significant differences. Mean Lysholm scores were 95.00±6.64 in hamstring vs 95.59±2.20 peroneus longus, p=0.662. The anterior drawer test grade 0 was observed in 59.3% of hamstring vs 70.4% peroneus longus, p=0.426. Conclusion: Peroneus longus autografts demonstrated comparable clinical outcomes to hamstring autografts in ACL reconstruction. The peroneus longus graft had predictable larger graft diameter, and better improvement in thigh muscle mass without significant ankle morbidity.